Obesity impairs general health-related quality of life (HR-QoL) in premenopausal women to a greater extent than polycystic ovary syndrome (PCOS) - Álvarez-Blasco, Francisco; Luque-Ramírez, Manuel; Escobar-Morreale, Héctor F. (Clinical endocrinology (Oxford), 2010)
Summary Objective  Obesity is frequently associated with the polycystic ovary syndrome (PCOS) and both conditions may impact on the health‐related quality of life (HR‐QoL) of affected patients. We aimed to estimate the relative impact of obesity and PCOS on the general HR‐QoL of premenopausal women. Design  Case–control study. Patients  Consecutive overweight and obese premenopausal women seeking advice for weight loss, of whom 32 were diagnosed with PCOS and 72 had no evidence of androgen excess and were considered controls. Measurements  Spanish versions of the Short Form 36 Health Survey (SF‐36) questionnaire and the Nottingham Health Profile (NHP) were self‐administered by the women. Results  Patients with PCOS and controls had similar body mass index, yet controls were older. General HR‐QoL mean scores were similar in both groups, yet patients with PCOS scored worse in the role‐emotional item of SF‐36, and controls scored worse in the pain item of NHP. Increasing grades of obesity, on the contrary, were associated with worse scores in the NHP, and SF‐36 items related to general and physical aspects of HR‐QoL. When compared with the standards established for the Spanish general population, both patients with PCOS and controls frequently presented with abnormal scores, yet only increasing grades of obesity were associated with more frequent abnormal scoring. Conclusions  Obesity impaired general HR‐QoL to a greater extent than PCOS in overweight and obese premenopausal women.